Asuhan Kebidanan Komprehensif pada Ny.R Umur 39 Tahun dengan Resiko Tinggi Umur di TPBM Ny.S Wilayah Kerja Puskesmas Kaliwadas Tahun 2025 - Ataniya Nazmu Naeda; Hafsah Habib Shodiq; Surni’ah Surni’ah (Jurnal Siti Rufaidah, 2026)
Maternal mortality remains a major global health concern and an important indicator of health system performance. The World Health Organization reported in 2023 that approximately 290,000 maternal deaths occurred worldwide, highlighting persistent challenges in maternal health services. In the ASEAN region, the maternal mortality rate in 2023 was recorded at 16.85 per 1,000 live births. In Indonesia, the Maternal Mortality Rate in 2023 reached 189 per 100,000 live births according to the Ministry of Health of the Republic of Indonesia. Significant progress has been observed in Central Java Province, where the rate decreased from the United Nations Sustainable Development Goals target of 226 per 100,000 live births to 88.11 per 100,000 live births in 2023. At the district level, Brebes Regency recorded 54 cases per 100,000 live births in 2023 and reported 54 maternal deaths in 2024. Meanwhile, the Kaliwadas Community Health Center reported no maternal deaths during 2023 and 2024, indicating relatively effective maternal health services at the local level.